Chinese Students Abroad: Dynamics of the Number and Aims of Educational Travel - S. S. Donetskaya; M. Li (Высшее образование в России)
This paper discusses the processes of the educational travel of the Chinese students abroad. Based on data of the Ministry of Education of China, publications from the Chinese Internet, original articles published in the world periodicals, the reasons elucidated why the number of students leaving China changed from 2001 to 2018; describes funding sources of educational travel. Information on the contemporary preferences of Chinese students in selection of countries and study programs, aims and reasons of educational travel abroad is provided. The hard competition of the young persons after school on educational services market, expected job difficulties after graduation from national universities and influence of parents are pushing young Chinese people to consider studying abroad. Over the past 10 years, the number of Chinese citizens studying in foreign universities rates more than doubled and reached to 662.1 thousand in 2018. The aim of such migration is not only acquiring advanced western knowledge or improving foreign language skills but also getting the so-called symbolic capital, which arises after graduation from the famous foreign universities. This capital will bring tangible employment benefits and future career privileges in the Chinese companies. Therefore, currently the largest number of Chinese young people seek to become students in English speaking countries, where the concentration of the best world universities included in the top-100 of international rankings is high. The modern professional preferences of Chinese students correspond to the development trends of the China’s national economy and science, and depend on the future employment and opportunity to receive the scholarships from the Government of China.